Elaborating the Antecedents of Purchase Intentions in Second- Hand Car Industry: Case Study in Kurdistan Region of Iraq - TALIM, SAFEEN RAFIQ; ALI, BAYAD JAMAL; TOP, CEMIL (The journal of contemporary issues in business and government, 2021)
The aim of this study was to elucidate the antecedents of purchase intentions of the secondhand market customers. In this regard, the data was collected from Kurdistan region of Iraq to test the impacts of antecedents. Collected data was composed of validity and reliability analysis. Regression analysis was used to test the impacts. Results reveal that price has significant negative impact on the purchase intention while product quality, safety, and serviceability had significant positive impact on the purchase intentions. Lastly, it was observed that oil consumption didn’t have a significant impact on the purchase intentions of the customers.